2019
DOI: 10.14742/ajet.4539
|View full text |Cite
|
Sign up to set email alerts
|

Creating mathematics formative assessments using LaTeX, PDF forms and computer algebra

Abstract: Formative assessment benefits both students and teaching academics. In particular, formative assessment in mathematics subjects enables both students and teaching academics to assess individual performance and understanding through students’ responses. Over the last decade, educational technologies and learning management systems (LMSs) are used to support formative assessment design. In mathematics, this is problematic because of the inflexibility of LMS and educational technology tools.  Automating formative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Along with the technologies mentioned above, case technologies are also used, which are the most effective in the study of the modules of the science cycle [23]. The authors [24] use computer technology to evaluate the effectiveness of educational technologies, and determine the indexes of achievement [25]. Many authors also note that high-quality mathematical training enables better formation of research competence [26,27].…”
Section: Resultsmentioning
confidence: 99%
“…Along with the technologies mentioned above, case technologies are also used, which are the most effective in the study of the modules of the science cycle [23]. The authors [24] use computer technology to evaluate the effectiveness of educational technologies, and determine the indexes of achievement [25]. Many authors also note that high-quality mathematical training enables better formation of research competence [26,27].…”
Section: Resultsmentioning
confidence: 99%
“…Studies at the augmentation level (n=60) employed online tests to gain better understanding of learners' current knowledge and provide additional learning opportunities. There was an emphasis on using online technologies to enable timely and often automated feedback (Herbert et al, 2019) or design tests that incorporated multimedia resources or sophisticated types of questions (Cerutti et al, 2019). These studies unanimously reported student appreciation of formative feedback from online tests (Chen & Chuang, 2012).…”
Section: Current Research Into Online Testsmentioning
confidence: 99%
“…All content displayed to the user is written as simple HTML or Textile, with LaTeX used for mathematical notation. Formative assessment benefits both studentsand teaching academics [12]. Most especially, formative assessment in mathematics subjects enables both students and teaching academics to assess individual performance and understanding through students' responses.…”
Section: Review Of Related Literaturementioning
confidence: 99%